2019
DOI: 10.1038/s12276-019-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine 3-monooxygenase is a critical regulator of renal ischemia–reperfusion injury

Abstract: Acute kidney injury (AKI) following ischemia–reperfusion injury (IRI) has a high mortality and lacks specific therapies. Here, we report that mice lacking kynurenine 3-monooxygenase (KMO) activity (Kmonull mice) are protected against AKI after renal IRI. We show that KMO is highly expressed in the kidney and exerts major metabolic control over the biologically active kynurenine metabolites 3-hydroxykynurenine, kynurenic acid, and downstream metabolites. In experimental AKI induced by kidney IRI, Kmonull mice h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 38 publications
1
54
0
Order By: Relevance
“…Knockout of one allele of QPRT recapitulates these effects and increases susceptibility to AKI compared with control mice, which could be prevented by augmenting NAD + metabolism with oral NAM supplementation. 589,590 The robust finding that the early rise of urinary quinolinate levels and the urinary quinolinate/tryptophan ratio are related to the probability of AKI and adverse outcomes in a cohort of >300 patients indicates that impaired NAD + metabolism leads to kidney injury in patients. 591 Additionally, boosting NAD + levels via inhibiting ACMSD (an enzyme restricts the de novo synthesis of NAD + from tryptophan) also protects against AKI after renal I/R injury.…”
Section: -Hk 3-hydroxykynureninementioning
confidence: 99%
See 1 more Smart Citation
“…Knockout of one allele of QPRT recapitulates these effects and increases susceptibility to AKI compared with control mice, which could be prevented by augmenting NAD + metabolism with oral NAM supplementation. 589,590 The robust finding that the early rise of urinary quinolinate levels and the urinary quinolinate/tryptophan ratio are related to the probability of AKI and adverse outcomes in a cohort of >300 patients indicates that impaired NAD + metabolism leads to kidney injury in patients. 591 Additionally, boosting NAD + levels via inhibiting ACMSD (an enzyme restricts the de novo synthesis of NAD + from tryptophan) also protects against AKI after renal I/R injury.…”
Section: -Hk 3-hydroxykynureninementioning
confidence: 99%
“…592,593 Moreover, due to the decrease of 3-hydroxykynurenine (a cytotoxic metabolite of KMO), the mice that lack active kynurenine 3-monooxygenase (KMO) will not develop into AKI after I/R injury. 590 The expression of PARPs in the injured kidney's proximal tubules is upregulated from 6-12 h after I/R injury. 594 Oxidative stress and DNA damage caused by I/R injury lead to excessive activation of PARPs.…”
Section: -Hk 3-hydroxykynureninementioning
confidence: 99%
“…KMO competes with kynurenine aminotransferases (KATs) that generate kynurenic acid. A 2019 study reported that global Kmo-knockout mice were less susceptible to renal IRI than wild-type controls 55 . This finding suggests an adaptive role of the suppression of de novo pathway enzymes, namely, the shunting of metabolic flux away from NAD + biosynthesis and towards the generation of kynurenic acid, which modulates inflammation, neuronal signalling and adaptive immunity 56 .…”
Section: Nadpmentioning
confidence: 99%
“…Aziz, Abdel‐Salam, Al‐Obaide, Alobydi, and Al‐Humaish () speculated that the identified miRNAs can regulate KMO expression by studying the 5′ and 3′ regulatory factors of the KMO gene, and in common with the alternative promoter of the 5′ regulatory region of KMO may help to develop smoking diagnosis and treatment. Zheng et al () found that inhibition of KMO activity helps to cure ischemia–reperfusion injury (IRI) after acute kidney injury (AKI). In addition, the activity of KMO as a causal factor for changes in the kidney leading to proteinuria (Korstanje et al, ) was increased significantly in chronic renal failure of various severity (Pawlak, Tankiewicz, Matys, & Buczko, ), and it may be a new research direction of kynurenine pathway.…”
Section: The Mechanism Of Kmo In Different Diseasesmentioning
confidence: 99%